1982
DOI: 10.3102/00346543052003446
|View full text |Cite
|
Sign up to set email alerts
|

Educational Seduction

Abstract: Critics have referred to the influence of an instructor’s personality on student ratings of instruction as the “Dr. Fox effect” or “educational seduction.” In reviewing earlier research, we found inconsistencies from study to study and conducted a meta-analysis to attempt an empirical integration of this literature. Overall, we found that instructor expressiveness had a substantial impact on student ratings but a small impact on student achievement. In contrast, lecture content had a substantial impact on stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(80 citation statements)
references
References 37 publications
3
77
0
Order By: Relevance
“…The positive outcomes associated with immediate teaching are numerous, and include increases in student affect for course material and instructors (Frymier, 1994;Richmond, 1990;Titsworth, 2001b), less decline in affect after encountering an instructor (Titsworth, 2001b), increased state motivation to learn (Christophel, 1990;Richmond, 1990), increased perceptions of self-control (Perry & Penner, 1990), higher ratings of instruction (Abrami, Leventhal, & Perry, 1982), increased perceptions of cognitive learning (Christophel, 1990;Richmond, 1990), and retention of course material (Kelley & Gorham, 1988;Messman & Jones-Corely, 2001;Perry & Penner, 1990;Witt & Wheeless, 2001). A more extensive review of the benefits of nonverbally immediate teaching is provided by Chesebro and McCroskey (1998).…”
Section: Nonverbal Immediacy and Clear Teachingmentioning
confidence: 99%
“…The positive outcomes associated with immediate teaching are numerous, and include increases in student affect for course material and instructors (Frymier, 1994;Richmond, 1990;Titsworth, 2001b), less decline in affect after encountering an instructor (Titsworth, 2001b), increased state motivation to learn (Christophel, 1990;Richmond, 1990), increased perceptions of self-control (Perry & Penner, 1990), higher ratings of instruction (Abrami, Leventhal, & Perry, 1982), increased perceptions of cognitive learning (Christophel, 1990;Richmond, 1990), and retention of course material (Kelley & Gorham, 1988;Messman & Jones-Corely, 2001;Perry & Penner, 1990;Witt & Wheeless, 2001). A more extensive review of the benefits of nonverbally immediate teaching is provided by Chesebro and McCroskey (1998).…”
Section: Nonverbal Immediacy and Clear Teachingmentioning
confidence: 99%
“…As field studies, they were well-controlled and very strict methodologically. Many other studies were equally well-controlled and used strict methodology (see, for example, Perry et al, 1979;Abrami, Leventhal, & Perry, 1982), but they used staged teaching simulations rather than naturally-occurring instructor behavior (see critique of the Doctor Fox studies in this chapter). 2.…”
Section: Methodological Note: Murray's 1983 Studies As Model Researchmentioning
confidence: 99%
“…Abrami et al (1982) eventually published an article entitled "Educational seduction," in which they meta-analyzed a dozen Doctor Fox studies. They concluded that instructor expressiveness had a substantial impact on student ratings but a small impact on student achievement.…”
Section: The Doctor Fox Phenomenonmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies the authors manipulated factors such as monetary compensation and whether the participant knew he or she would be tested on the content, and the results showed how important the Dr Fox effect may be in the specific context of a narrative. Overall, the authors found that the instructor’s expressiveness had a significant impact on student ratings of teacher effectiveness but not on student achievement, whereas lecture content had an impact on achievement but not ratings [47]. The greatest effect on ratings was seen when there was no external motivation to learn, such as money or testing [48]; that is, the instructor’s performance had the greatest effect in contexts most like everyday narratives: where the interlocutor is not being either paid to listen or tested on the content.…”
Section: Introductionmentioning
confidence: 99%